Robusta and Arabica Coffee Effects on Yoghurt’s Physical, Chemical, Sensory, and Microbiological Quality - Jannah, Syerina Raihatul; Verawati, Endang; Manurung, Nancy Eka Putri; Sulastriani; Kalista, Ayu (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study entitled robusta and arabica coffee effects on yoghurt’s physical, chemical, sensory, and microbiological quality. Aimed to investigate the impact of adding Robusta coffee, Arabica coffee, and their combination on the physicochemical properties and sensory acceptance of yoghurt. The research was structured using a Completely Randomized Design, analyzing six distinct formulations, including a control (A), pure coffees (B, C), and combinations (D, E, F). Data analysis utilized ANOVA followed by the Honestly Significant Difference test. Sensory evaluation identified treatment E as the most preferred overall (score 4.00), owing to its strong, yet well-balanced, coffee flavor and aroma. Further analysis focused on treatment E, assessing viscosity, color, and total Lactic Acid Bacteria count. Results indicated that coffee inclusion significantly influenced all parameters. Treatment E exhibited the highest pH (4.85) and showed a dramatic viscosity decrease from 727.5 (control) to 37.5 cP. Color analysis revealed a darker product (L* 63.93), with significant increases in a*, b*, C*, and H* values, attributed to coffee's melanoidin content. Importantly, the total LAB count for treatment E (4.5 × 10⁷ CFU/ml) was statistically similar to the control and met the minimum national standard (SNI 01-2981-2009). In conclusion, Formulation E successfully yielded a functional coffee yoghurt product with excellent organoleptic characteristics and preserved the viability of Lactic Acid Bacteria.